2005
DOI: 10.1084/jem.20041924
|View full text |Cite
|
Sign up to set email alerts
|

The BCL2A1 gene as a pre–T cell receptor–induced regulator of thymocyte survival

Abstract: The pre–T cell receptor (TCR) is expressed early during T cell development and imposes a tight selection for differentiating T cell progenitors. Pre-TCR–expressing cells are selected to survive and differentiate further, whereas pre-TCR− cells are “negatively” selected to die. The mechanisms of pre-TCR–mediated survival are poorly understood. Here, we describe the induction of the antiapoptotic gene BCL2A1 (A1) as a potential mechanism regulating inhibition of pre–T cell death. We characterize in detail the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 48 publications
10
143
2
1
Order By: Relevance
“…This result correlates with the increased susceptibility of CD4 1 Foxp3 À CD5 À/À thymocytes to apoptosis. In this context, Akt was shown to play a role in thymocyte survival [63,64], through the induction of Bcl-2 family members, such as Bcl-XL [65] and A1 [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result correlates with the increased susceptibility of CD4 1 Foxp3 À CD5 À/À thymocytes to apoptosis. In this context, Akt was shown to play a role in thymocyte survival [63,64], through the induction of Bcl-2 family members, such as Bcl-XL [65] and A1 [66].…”
Section: Discussionmentioning
confidence: 99%
“…This result correlates with the increased susceptibility of CD4 1 Foxp3 À CD5 À/À thymocytes to apoptosis. In this context, Akt was shown to play a role in thymocyte survival [63,64], through the induction of Bcl-2 family members, such as Bcl-XL [65] and A1 [66].In contrast to naïve thymocytes, the absence of CD5 did not affect Akt phosphorylation in Treg, in response to TCR crosslinking. Interestingly, Bensinger et al [67] recently showed that peripheral Treg, stimulated in the presence of IL-2, show increased survival in the absence of Akt phosphorylation, suggesting that Akt activation is dispensable for Treg survival.…”
mentioning
confidence: 99%
“…A1 expression is markedly upregulated in immature T cells during the process of pre-TCR selection, 38,39 suggesting that A1 may promote cell survival during this critical developmental stage. Accordingly, the A1 knockdown mouse model had an increase in DN2 and DN3 thymocytes and a corresponding reduction in the DN4 and DP populations.…”
Section: Figure 1 For Caption See Page 536mentioning
confidence: 99%
“…As such, although overexpression of Bfl-1 alone was not tumorigenic in mice 391 , Bfl-1 overexpression led to increased E1A-induced transformation 392 , and enhanced mycinduced leukemogenesis 393 . It has also been suggested that Bfl-1 contributes to the transformation of pre-T-cells when T-cell receptor signalling is deregulated 394 and that, along with CEBP, Bfl-1 is essential for anaplastic lymphoma kinase (ALK)-driven transformation to anaplastic large cell lymphoma 387 .…”
Section: The Role Of Bfl-1 In Cancermentioning
confidence: 99%